Factors influencing the oxygen concentration gradient from the synovial surface of articular cartilage to the cartilage-bone interface: a modeling study. - Zhou, S; Cui, Z; Urban, J (2004)
OBJECTIVE: There is very little information on the gradients of oxygen concentration from the synovial surface to the subchondral bone in articular cartilage. Cartilage is usually regarded as hypoxic, even though cellular metabolism is inhibited at low oxygen concentrations. We therefore measured rates of cellular consumption of oxygen and used these rates to calculate oxygen tension profiles across articular cartilage. METHODS: The rate of oxygen consumption by bovine articular chondrocytes was measured in vitro, either in intact cartilage slices or in isolated chondrocytes. The oxygen tension profile across articular cartilage was predicted by solving a 1-dimensional reaction-diffusion equation. The effect of synovial fluid oxygen concentration, cell density, cartilage thickness, and influx of oxygen from the subchondral bone on the oxygen profile in the tissue was examined. RESULTS: Oxygen consumption rates were relatively independent of oxygen tension at high oxygen tensions (5-21%), where they were approximately 10 nmoles/10(6) cells/hour for both isolated chondrocytes and for cartilage slices. Below 5% oxygen, the rate fell in an oxygen tension-dependent manner. Analysis showed that the oxygen profile across cartilage fell steeply in all but the thinnest cartilage samples but only fell to approximately 1% for low oxygen tensions in synovial fluid, with no supply from the subchondral bone. CONCLUSION: The oxygen tension in normal cartilage is not likely to fall to 1% except under abnormal conditions. Oxygen tensions within cartilage are strongly affected by a number of factors, including oxygen concentrations in synovial fluid, cartilage thickness, cell density, and cellular oxygen consumption rates. Supply from the subchondral bone may be of particular importance.